2010
DOI: 10.1007/s10549-010-0866-3
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab and osteonecrosis of the jaw: incidence and association with bisphosphonate therapy in three large prospective trials in advanced breast cancer

Abstract: Long-term bisphosphonate therapy is associated with increased risk of osteonecrosis of the jaw (ONJ). In a retrospective analysis, a 16% ONJ incidence was reported in patients receiving bisphosphonates with antiangiogenic therapy (bevacizumab or sunitinib) for bone metastases from breast, colon, or renal cell cancers. To assess ONJ incidence with bevacizumab, we analysed data from 3,560 patients receiving bevacizumab-containing therapy for locally recurrent or metastatic breast cancer (LR/MBC) in two double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
166
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(177 citation statements)
references
References 40 publications
2
166
0
9
Order By: Relevance
“…ONJ cases after bevacizumab alone were observed in colorectal, breast, lung, parotid gland, and renal cancer patients, and revealed differentiated clinical history and outcome. [12,18,[71][72][73][74][75][76] Furthermore, one case was observed after intravitreous bevacizumab. [77] Some other published cases are notable: one pancreatic cancer patient showed ONJ during treatment with bevacizumab and sorafenib [78] and one renal cell cancer patient had received bevacizumab plus temsirolimus [79]; another renal cell cancer patient developed ONJ during bevacizumab treatment, after previous treatments with sunitinib and temsirolimus.…”
Section: Bevacizumabmentioning
confidence: 99%
See 2 more Smart Citations
“…ONJ cases after bevacizumab alone were observed in colorectal, breast, lung, parotid gland, and renal cancer patients, and revealed differentiated clinical history and outcome. [12,18,[71][72][73][74][75][76] Furthermore, one case was observed after intravitreous bevacizumab. [77] Some other published cases are notable: one pancreatic cancer patient showed ONJ during treatment with bevacizumab and sorafenib [78] and one renal cell cancer patient had received bevacizumab plus temsirolimus [79]; another renal cell cancer patient developed ONJ during bevacizumab treatment, after previous treatments with sunitinib and temsirolimus.…”
Section: Bevacizumabmentioning
confidence: 99%
“…We have already reported the initial experience from Memorial Sloan Kettering Cancer Center. [51] In 2010, a retrospective study on breast cancer patients revealed a very low risk after bevacizumab alone (0.3-04%) in comparison with the combination of bevacizumab and BPs (0.9-2.4% range) within a large trial population [12] However, only ONJ cases with frank bone exposure were registered in that analysis, and median follow-up of groups ranged only between 10 and 19 months. Were ONJ cases in bevacizumab-treated patients somewhat different from BRONJ cases?…”
Section: Bevacizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it is reported that osteonecrosis of jaws cases associated with other antiresorptive (denosumab) and antiangiogenic therapies increase gradually. [15] Therefore, a change was needed to accommodate the term of BRONJ. In 2014, American Association of Oral and Maxillofacial Surgeons (AAOMS) recommended that the term "Bisphosphonate-related Osteonecrosis of The Jaw" (BRONJ) be replaced with the new terminology ''Medication-related Osteonecrosis of the Jaw'' (MRONJ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF inhibitors work somewhat more directly to inhibit the osteoclasts through their action on monocytes which then are in the osteoclast developmental feedback loop. Further reading on these medications will be left to the reader for exploration [30][31][32][33][34][35][36][37][38][39][40].…”
Section: History and Medication Review Of Osteochemonecrosismentioning
confidence: 99%